Perkataan Arab dalam Bahasa Melayu: Satu Tinjauan dari Aspek Morfologi - Yusoff, Mohd Alwee; Mohamed Adnan, Mohamad Azrien (Jurnal Usuluddin, 2009)
This article discusses the use of Arabic words in Malay language. The existence of Arabic terminologies in Malay language has enhanced Malay language as knowledge and civilization language. There are many Arabic terminologies that have been used in Malay language related to worship, Islamic transaction as well as science and technology. In this case, Malay Muslim scholars have played an important role in developing Malay language by transferring the Arabic vocabularies into Malay vocabularies. Studies regarding Arabic terminologies used in Malay language from the aspect of morphology can be seen through the phonetic transformation and the augmented